Family Dispute Resolution System and Its Challenges in Indonesia - Maghrabi, Ahmad Maulana; Abdul Basith, Muhammad; Sururie, Ramdani Wahyu (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The The family dispute resolution system in Indonesia aims to resolve various issues within family relationships, such as divorce, child custody, and division of joint property. Dispute resolution can be conducted through two main channels: litigation (court proceedings) and non-litigation (mediation). The court plays an important role in enforcing the law and protecting the rights of the parties involved. This article aims to analyze the effectiveness of the family dispute resolution system in Indonesia and evaluate the challenges faced in its implementation. The discussion begins with an explanation of the dispute resolution system in court, mediation as an alternative dispute resolution method, and the challenges in resolving family disputes in Indonesia. Furthermore, the article examines the role of the court in supporting justice for the parties involved in family disputes and identifies factors that affect the success of mediation. This study is also necessary to explore the challenges and dynamics that arise in family dispute resolution, particularly regarding the duration of legal processes, high costs, and emotional tensions between the disputing parties. This research uses a qualitative method, referring to related sources such as previous studies on family dispute resolution. In conclusion, the family dispute resolution system in Indonesia requires improvements, including the optimization of mediation, simplification of legal procedures, and digitalization of legal services to achieve a more efficient and just process